Characterization of the global metabolic profile of liquiritin in rat plasma, urine, bile and feces based on UHPLC-FT-ICR MS. Issue 11 (5th February 2018) - Ma, Li; Zhao, Yangyang; Zhang, Xiaoxue; Liu, Tianfeng; Han, Fei; Yin, Ran
Abstract : Liquiritin is a major flavonoid in Radix Glycyrrhizae and it has been reported to possess various pharmacological activities. Abstract : Liquiritin is a major flavonoid in Radix Glycyrrhizae and it has been reported to possess various pharmacological activities. In the present work, a strategy based on an ultra high performance liquid chromatography combined with Fourier transform ion cyclotron resonance mass spectrometry (UHPLC-FT-ICR MS) method was proposed to systematically characterize the in vivo metabolites of liquiritin for the first time. After oral administration of liquiritin to rats in a single dose of 120 mg kg −1, the rat plasma, urine, feces and bile samples were collected and used to discover metabolites. As a result, besides the parent drug, a total of 76 metabolites (6 phase I and 70 phase II metabolites) of liquiritin were detected and tentatively identified. It was indicated that the metabolic pathways of liquiritin in rats included oxidation, reduction, deglycosylation, isomerization, methylation, glucuronidation and sulfation. In summary, the results could provide valuable information regarding the metabolism of liquiritin in rats, which could contribute to a better understanding of its action mechanism.